Case Report: Grade 4 pneumonitis occurred after thoracic radiotherapy and dacomitinib in a patient with lung adenocarcinoma - Liu, Ailing; Wen, Junxu; Zhao, Kaikai; Jiang, Liyang; Meng, Xiangjiao (Frontiers in Oncology, 2025)
Osimertinib combined with chest radiotherapy has a high incidence of pneumonia, dacomitinib is widely used in clinical practice, but there are no studies reporting the pulmonary safety of dacomitinib in combinating with radiotherapy. Here we report a case of radiation pneumonitis occurring by dacomitinib and thoracic radiotherapy (TRT). The patient was a 55-year-old woman with lung adenocarcinoma. She had received surgery and adjuvant chemotherapy. The patient presented with bilateral intramammary and para-aortic metastatic lymphadenopathy, which was confirmed as metastasis, and subsequently received treatment with dacomitinib. Radiotherapy started after 4 months of dacomitinib. The Clinical Target Volume (CTV) was metastatic lymph nodes area. The prescription dose was 60 Gy/30F. The mean lung dose (MLD), V20, and V5 were 8.16Gy, 16%, and 34.5%. Despite the lung V20 and mean lung dose being exceptionally low, the patient exhibited respiratory symptoms, and a CT chest scan revealed grade 4 radiation pneumonitis two weeks following the conclusion of radiotherapy. The radiotherapy and dacomitinib were discontinued, and immediate initiation of pulmonary anti-inflammatory treatment ensued. The concurrent administration of dacomitinib and RT carries the risk of inducing serious pneumonia. This case highlights the potential risk of severe pneumonia associated with this combination therapy, emphasizing the need for further research to clarify its safety and develop effective management strategies.